Sociocultural Factors Influencing The Willingness To Learn The Skills Of Translation Among Iranian Students - Akbarimotlaq, Mohammadjavad (2023)
The purpose of this study is to explore the sociocultural factors influencing Iranian professional translation learners’ WTLT (willingness to learn translation) to identify the sociocultural factors that influence WTLT and investigate their relationship, also to investigate the influence of age and gender on WTLT. This study adopts the mixed method approach that contains two phases. The data from the first phase, which is qualitative: FGD (Focus Group Discussion), informs the development of the second research instruments, questionnaire for the quantitative phase. The population of this study is 200 Iranian translation students. For the 1st phase, 20 participants were purposively selected to participate in the FGD. The data from the FGD were analyzed. Enthusiasm to translate, enthusiasm to translate technical text, enthusiasm to translate informal text, enthusiasm to translate scientific text, and enthusiasm to earn money from translation were the factors found influencing willingness to learn translation. The themes created were used to form the questionnaire. The next phase dealt with the validation of the designed questionnaire by employing exploratory factor analysis and structural equation modeling as confirmatory factor analysis. The WTLT questionnaire was distributed to 200 professional translation students that were selected based on convenient sampling technique and the Pearson-product moment correlation was used to determine whether there is a direct and significant relationship between the enthusiasm factors and willingness to learn translation. The results indicated a significant and positive correlation.